IMPROVING NITROGEN FERTILIZER ABSORPTION AND ITS EFFECT ON QUALITY AND SEED YIELD OF CORN (Zea mays) - Kuswanto Kuswanto; Karuniawan Puji Wicaksono; Sudakir Sudakir; Edson Begliomini (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2013)
Improving nitrogen uptake by pyraclostrobin application in maize under green house and field conditions were investigated. There were three series experiments conducted in dry season, 2011 and 2012. The research conducted using nested design and three replications. Nested design applied to get information as careful as possible about the role of treatment, especially the main factor. The first and second experiments hold at field and green house and the third experiment hold at green house. They had two factors, pyraclostrobin application and nitrogen fertilizer. Vegetative growth, flowering and earing age, chlorophyll content, yield, amylose and protein content evaluated. Application of pyraclostrobin, significantly increase nitrogen fertilizer efficiency. Amylose content and fresh yield were different on nitrogen and pyraclostrobin application. Application of pyraclostrobin 400 ml/ha significantly increase amylose 10.85-18.5%. Both of amylose and protein content were increased by nitrogen fertilizer application. Vegetative growth and chlorophyll content were affected by nitrogen and pyraclostrobin. Keywords: corn, N efficiency, pyraclostrobin, amylose, yield